Detection of boronic acid derivatives in cells using a fluorescent sensor1. Issue 25 (7th July 2015) - Hattori, Yoshihide; Ishimura, Miki; Ohta, Youichirou; Takenaka, Hiroshi; Watanabe, Tsubasa; Tanaka, Hiroki; Ono, Koji; Kirihata, Mitsunori
<x xml:space="preserve">Abstract</x> To develop a detection method for boronic acid derivatives, boron-chelating ligands were synthesized as fluorescent sensors for boronic acid derivatives.